Teori Produksi dalam Islam - Imroatus Sholiha (Fakultas Ekonomi dan Bisnis Islam, 2018)
Production is mandatory to meet the needs of the people, so this is the reason why Islam encourages people to utilize the existing natural resources to meet human needs by way of processing and producing it. Islam also regulates how man should be a good producer by referring to the existing production theory in Islamic economics. Therefore the purpose of this article is to provide information, describe or member knowledge to the general public and producers in particular so that it can understand how Islam actually organize and explain the theory of production. And this research is descriptive qualitative research. Descriptive technique used is literature study is to find information through books, journals and others. And the result of his research is that in Islam a producer is given limitations in producing, but not necessarily limited in creativity but a Muslim producer is prohibited to produce unlawful goods. And there are differences in the theory of Islamic production with conventional production theory that is in terms of cost, acceptance and amount of production. If in theory conventional production recognizes the interest pattern in production cost is different with the theory of Islamic production. This theory does not recognize the pattern of interest but which is a cooperation that will end production will be determined for the results of what use revenue sharing, profit sharing or profit and loss sharing depending on the agreement agreed at the beginning of cooperation.